2009
DOI: 10.1038/nn.2318
|View full text |Cite
|
Sign up to set email alerts
|

Myosin-dependent targeting of transmembrane proteins to neuronal dendrites

Abstract: The distinct electrical properties of axonal and dendritic membranes are largely a result of specific transport of vesicle-bound membrane proteins to each compartment. How this specificity arises is unclear because kinesin motors that transport vesicles cannot autonomously distinguish dendritically projecting microtubules from those projecting axonally. We hypothesized that interaction with a second motor might enable vesicles containing dendritic proteins to preferentially associate with dendritically project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
183
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(192 citation statements)
references
References 49 publications
6
183
2
1
Order By: Relevance
“…By combining this approach with a number of quantitative analyses, we provided evidence that two dendritic ion channels, Kv2.1 and Kv4.2, are precisely sorted into distinct pools of transport vesicles that are targeted to specific dendritic subcompartments by different molecular mechanisms. Previous work has demonstrated that membrane proteins targeted to either axonal or somatodendritic compart- ments, such as the transferrin receptor and neuroglia cell adhesion molecule (NgCAM) are sorted in distinct populations of transport vesicles (1), a result that has also been supported by recent studies (37,38). Our study further extends this compartment-specific trafficking model to ion channels that are localized to specific subcompartments within the dendrites.…”
Section: Discussionsupporting
confidence: 84%
“…By combining this approach with a number of quantitative analyses, we provided evidence that two dendritic ion channels, Kv2.1 and Kv4.2, are precisely sorted into distinct pools of transport vesicles that are targeted to specific dendritic subcompartments by different molecular mechanisms. Previous work has demonstrated that membrane proteins targeted to either axonal or somatodendritic compart- ments, such as the transferrin receptor and neuroglia cell adhesion molecule (NgCAM) are sorted in distinct populations of transport vesicles (1), a result that has also been supported by recent studies (37,38). Our study further extends this compartment-specific trafficking model to ion channels that are localized to specific subcompartments within the dendrites.…”
Section: Discussionsupporting
confidence: 84%
“…This expectation is consistent with results from live-cell motility assays showing that the addition of myosinVb motors to cargos can arrest kinesin-2-dependent vesicle motions (31). Such responses are also consistent with observations that myosinV motors play key roles in neuronal trafficking processes while interacting with kinesins (32). Fully confirming such behavior will require further investigations and assays using additional cell types.…”
Section: Myosinva Motors Work Better As a Team Than Kinesinsupporting
confidence: 89%
“…For example, ChETA is a ChR2 genetic variant that has faster opening and closing rates than ChR2, with a reduced photocurrent amplitude (Gunaydin et al 2010), whereas ChEF demonstrates slower temporal kinetics, but increased light sensitivity (Lin et al 2009). ChR2 is also being targeted to specific regions of the neuron, such as the dendrites (Lewis et al 2009) and the axon (Lewis et al 2011). When ChR2 was limited to the axon initial segment (Grubb and Burrone 2010), action potentials could not be generated, presumably due to the small number of channels available for recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Our model predicts that redistributing ChR2 to the apical dendrites for apical directed stimulation may decrease irradiance levels by up to threefold. Recent advances in the development of not only neuron-specific, but also neuron section-specific, promoters for ChR2 (Lewis et al 2009) suggest that such channel distributions are possible. This concept could be especially advantageous for large volume optical stimulation with LEDs that rest on the cortical surface, while still targeting selective activation of layer V pyramidal neurons.…”
Section: Discussionmentioning
confidence: 99%